2020
DOI: 10.1289/ehp5751
|View full text |Cite
|
Sign up to set email alerts
|

Design and Rationale of the Biomarker Center of the Household Air Pollution Intervention Network (HAPIN) Trial

Abstract: BACKGROUND: Biomarkers of exposure, susceptibility, and effect are fundamental for understanding environmental exposures, mechanistic pathways of effect, and monitoring early adverse outcomes. To date, no study has comprehensively evaluated a large suite and variety of biomarkers in household air pollution (HAP) studies in concert with exposure and outcome data. The Household Air Pollution Intervention Network (HAPIN) trial is a liquified petroleum gas (LPG) fuel/stove randomized intervention trial enrolling 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 87 publications
0
19
0
Order By: Relevance
“…Investigators in the Household Air Pollution Intervention Network (HAPIN) trial initially suspended data collection due to the pandemic and have since restarted collection of behavioural, environmental, biological and clinical measurements in the fth year of a ve-year, multi-country trial. [5][6][7][8] HAPIN is a randomized controlled trial in Guatemala, India, Peru, and Rwanda that is assessing the health bene ts of providing lique ed petroleum gas (LPG) stoves and an 18-month supply of free LPG to 3,200 households that otherwise depend on solid biomass fuel (wood, animal dung, or crop residue) for cooking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigators in the Household Air Pollution Intervention Network (HAPIN) trial initially suspended data collection due to the pandemic and have since restarted collection of behavioural, environmental, biological and clinical measurements in the fth year of a ve-year, multi-country trial. [5][6][7][8] HAPIN is a randomized controlled trial in Guatemala, India, Peru, and Rwanda that is assessing the health bene ts of providing lique ed petroleum gas (LPG) stoves and an 18-month supply of free LPG to 3,200 households that otherwise depend on solid biomass fuel (wood, animal dung, or crop residue) for cooking.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of cooking behavior, personal and in-home exposure to air pollution, biological samples and clinical measurements are being collected longitudinally from pregnant women and their newborns in every household, along with an older adult woman, if present. [5][6][7][8] Our study involves home visits, as well as visits to health centers and hospitals during the woman's pregnancy and the rst year of the child's life.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, although our analysis will focus on PM 2:5 as our primary pollutant, black carbon and CO estimates will be incorporated into exposure-response models and may provide new insights into their health implications either as independent predictors or in combination. The exposure measurements will also be evaluated in conjunction with the planned biomarker assessments (e.g., urinary PAHs and levoglucosan) (Boyd Barr et al 2020), allowing mediation analysis to assess whether the biomarkers may be intermediate variables between exposure and health effects.…”
Section: Discussionmentioning
confidence: 99%
“…Here we summarize our methods used for estimating personal exposure for the HAPIN participants. A description of the overall trial methods can be found in the paper by Clasen et al (2020) and a description of the biomarker methods, including repeated measures of biomarkers of exposure [e.g., urinary polycyclic aromatic hydrocarbons (PAHs), levoglucosan], can be found in the paper by Boyd Barr et al (2020). Our methods build on previous efforts while making use of newer approaches and tools with the aim of maximizing the quality and accuracy of personal exposure estimates.…”
Section: Introductionmentioning
confidence: 99%
“…Using urine and DBS collected at regular intervals from the pregnant woman, older adult woman, and child (Table 1), the Biomarker Center will: a) assess repeated measures, including targeted biomarkers of exposure, biomarkers of tobacco smoke exposure, biomarkers of effect that are predictive of clinical outcomes, and exploratory analyses that include metabolomics, mRNA, miRNA, and DNA methylation; b) perform HAP-specific biomarker development and validation; c) create and operate a biospecimen repository; and d) create a data set for deposit in the National Institutes of Health (NIH) BioLINCC repository and ensure that study procedures are compatible with that program's requirements for biospecimen collection, labeling, and storage. Biomarker sampling methodologies are described in detail elsewhere (Barr et al 2020;Hu et al 2000;Liu et al 2014).…”
Section: Biomonitoringmentioning
confidence: 99%